(untitled) (Development Service Industry Management, 2024)
The article examines the milestones of the development of the business environment through the prism of industrial revolutions and the theory of spiral dynamics of organizational development. The past influences the present. The present shapes the future. The world is a complex, interconnected whole that is difficult to represent and understand, especially regarding complex socio-economic processes and organizational systems, including enterprises. The first radical change began precisely with the agrarian revolution when people domesticated animals as a basis for the transition from gathering to agriculture. After the agrarian revolution, radical industrial changes began in the 18th century. The first industrial revolution (from the 1760s to the 1840s) - the invention of the steam engine and the construction of railways. The second industrial revolution (the end of the 19th and the beginning of the 20th century) - the emergence of mass production thanks to the invention of electricity and the introduction of the conveyor. The third industrial revolution, from the 1960s, - was the emergence of semiconductors and their use in large electronic computing machines, personal computers, and the Internet. The fourth industrial revolution began at the beginning of the 21st century and is characterized by the emergence of "smart enterprises". The content and essential components of these periods imposed and imposed their understanding on the development of organizational models and the way of interaction between stakeholders and the economic entities themselves, which arose at the later stages of development and are developing under the influence of global business trends. Deepening the understanding of the nature of modern approaches in management aimed at the development of organizational systems allows turning to the past and investigating issues of organizational models on the way of the history of human development based on the theory of spiral dynamics (Don et al.), which is based on a dynamic model of human development and evolution of her consciousness, change of fundamental values. So, from the standpoint of the concept of systemic perfection of a business organization, based on the theory of spiral dynamics, its consideration can be started in the system-wide understanding of the system state, which corresponds to a greater extent to the content of perfection - from the orange stage and more/less corresponds to the current trends of the fourth industrial revolution. A significant strategic gap occurs based on the mismatch between the stage of development according to the milestones of industrial revolutions and the organization’s current state in relation to the theory of spiral dynamics. For example, a red organization that functions in the fourth industrial revolution era. Management of changes in paradigms of thinking is the art of management.